Donkey milk microbiota : isolation and characterization for potential applications - Aspri, Maria (Department of Agricultural Sciences, Biotechnology and Food Science, Faculty of Geotechnical Sciences and Environmental Management, Cyprus University of Technology, 2017)
Milks from non traditional animal species (i.e., donkey, camel, and buffalo) are recently gaining momentum mainly due to the fact that they are considered suitable to supplement the needs of special population groups (i.e., infants, the elderly). Research on donkey milk has dramatically increased over the past few years; therefore, this study aims to critically summarize the current research, characterizing the microbiota diversity of donkey milk and finally offering an insight into its unique functional properties, namely, antimicrobial, antioxidant and ACE-inibitory activities. The purpose of this project was to provide general information about donkey milk produced in Cyprus by characterizing and identifying the microbiota diversity of raw donkey milk, for potential application into the production of a nutraceutical fermented donkey drink. The project consists of four main parts. There has been a trend recently to isolate wild-type strains from natural sources for use as starter cultures in food fermentation. Therefore, the first part of the project has concentrated on the study of the diversity, technological and the safety aspects of LAB isolated from raw donkey milk, in order to determine their potential to be used as starters/adjuncts cultures in dairy products. Gram-positive, catalase negative bacteria (257) were isolated using selective microbiological media from eleven raw milk samples, collected over seven months from a donkey farm in Cyprus. All isolates were identified by phenotypic and molecular methods. Organisms identified with partial 16S rDNA sequence analysis were classified within the genus of Lactobacillus, Leuconostoc, Streptococcus and Enterococcus. Following identification, the predominant LABs were assessed for technological properties; acidification capacity, proteolytic, lipolytic and autolytic activities and production of exopolysaccharides (EPS) and diacetyl. Furthermore, in order to assess their suitability as starter/adjunct cultures, their susceptibility to antibiotics, the absence of virulence factors, the lack of haemolytic activity and production of biogenic amines were also investigated. The safety profile of the isolates revealed that their great majority were susceptible to clinically important antibiotics (i.e. vancomycin) and production of biogenic amines (i.e. tyramine) while the presence of some virulence genes occurred in a few isolates.
Keywords: Donkey milk; LAB; Bacteriocins; Probiotics; Bioactive Peptides